2015
DOI: 10.1007/s00247-015-3375-z
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic appearances of the epididymis in boys with acute testicular torsion but preserved testicular blood flow on color Doppler

Abstract: The position and morphology of the head of the epididymis were abnormal in all boys with acute testicular torsion but with preserved testicular flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 18 publications
1
7
0
2
Order By: Relevance
“…This finding is consistent with a previous report showing that the vast majority of patients with testicular torsion showed enlarged epididymal volume and hyperechogenicity on ultrasonography [9,11]. Galina et al [24] also focused on the abnormal configuration, size, and displaced position of the epididymis in patients with torsion and suggested that careful ultrasonographic evaluation of the epididymis may be useful as an adjunctive tool to diagnose testicular torsion. We demonstrated testicular hyperechogenicity and heterogeneity as early as 6 hours after complete torsion, but found no consistent patterns of echotexture change beyond 6 hours, whereas a previous study found that preoperative heterogeneous parenchymal echotexture indicated late torsion and testicular nonviability [10].…”
supporting
confidence: 91%
“…This finding is consistent with a previous report showing that the vast majority of patients with testicular torsion showed enlarged epididymal volume and hyperechogenicity on ultrasonography [9,11]. Galina et al [24] also focused on the abnormal configuration, size, and displaced position of the epididymis in patients with torsion and suggested that careful ultrasonographic evaluation of the epididymis may be useful as an adjunctive tool to diagnose testicular torsion. We demonstrated testicular hyperechogenicity and heterogeneity as early as 6 hours after complete torsion, but found no consistent patterns of echotexture change beyond 6 hours, whereas a previous study found that preoperative heterogeneous parenchymal echotexture indicated late torsion and testicular nonviability [10].…”
supporting
confidence: 91%
“…A partially twisted cord can have flow throughout its extent and might even look hyperemic (Fig. 4 ) [ 9 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…Both testicular MRI and contrast-enhanced sonography in the future might be a useful complement to clinical and baseline imaging in difficult/sonographically equivocal cases, although there are no prospective studies in the pediatric population [ 23 ]. In a retrospective study by Galina et al [ 9 ], the epididymis was always sonographically abnormal in boys with testicular torsion, being minimally or grossly displaced in relation to the testis and spermatic cord.…”
Section: Introductionmentioning
confidence: 99%
“…Galina et al [23] showed that the position and morphology of the epididymal head were abnormal in all nine of the boys in that study with acute testicular torsion but preserved testicular flow. This was also true in four cases with apparently normal-looking spermatic cords.…”
Section: Testicular Torsionmentioning
confidence: 86%
“…Thus, observation of the epididymis is especially important in cases of incomplete torsion with preserved testicular flow. Additionally, reactive hydrocele and scrotal wall thickening may be seen [7,23,24]. …”
Section: Testicular Torsionmentioning
confidence: 99%